2020
DOI: 10.1007/s10620-020-06644-1
|View full text |Cite
|
Sign up to set email alerts
|

Incident Dementia in Elderly Patients with Nonalcoholic Fatty Liver Disease in Germany

Abstract: Dementia and NAFLD are two frequent conditions that share underlying risk factors mainly in the realm of metabolic disease. Additionally, an association between NAFLD and brain aging has been proposed. Therefore, we investigated the hypothesis if NAFLD is an independent risk factor for emerging dementia. In this population-based cohort study, elderly patients (≥ 65 years) with NAFLD diagnosed between 2000 and 2015 were matched 1:1 to a cohort without NAFLD based on ICD-10 coding in the Disease Analyzer databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 28 publications
1
54
1
Order By: Relevance
“…In a 3-year follow-up study, Elliott and colleagues demonstrated that patients with NAFLD had faster cognitive decline compared to the general population (11). However, other studies have failed to demonstrate such a relationship (15,16). It remains open to question whether the relationship is an epiphenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 3-year follow-up study, Elliott and colleagues demonstrated that patients with NAFLD had faster cognitive decline compared to the general population (11). However, other studies have failed to demonstrate such a relationship (15,16). It remains open to question whether the relationship is an epiphenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A population with NAFLD were more likely to have impaired cognitive performance as compared with a healthy population (11)(12)(13)(14). However, most of the previous studies were crosssectional, which cannot assess the long-term effect of NAFLD on cognitive function (15,16). In addition, it was also unexplored whether the effect of NAFLD on subsequent cognitive impairment is modified by age, gender and carotid stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found no increased risk of dementia in elderly patients with NAFLD, which corroborates with our results. 23 Apart from this, limited clinical studies examining cognitive functioning in NAFLD patients have provided varying and conflicting results, [6] , [7] , [8] , 10 discrepancies that might be as a result of methodological differences ( e.g. use of different cognitive tests and the mean ages of the study population).…”
Section: Discussionmentioning
confidence: 99%
“…Another population-based study found that physically frail NAFLD patients with high risk of liver fibrosis were at a 5-fold increased risk of receiving a dementia diagnosis over a 8-year period, while physical frailty nor high risk of liver fibrosis were independent risk factors on their own [ 125 ]. Conversely, a third study found NAFLD not to be associated with a dementia diagnosis over a 10-year period in elderly patients ≥ 65 years [ 126 ]. In MRI brain studies, NAFLD was independently associated with reduced total brain volume, corresponding to 4.2 years of brain aging when compared with age-matched controls, as estimated by Weinstein et al [ 114 , 117 ].…”
Section: Possible Mechanisms Behind Cognitive Dysfunction In Nafldmentioning
confidence: 99%